Genetic characterization of Greek chestnut (Castanea sativa Mill.) germplasm collections in Parnon mountain - Ioannis MANTHOS; Lefkothea KARAPETSI; Thomas SOTIROPOULOS; Aliki XANTHOPOULOU; Panagiotis MADESIS (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
The European chestnut (Castanea sativa Mill.) is a unique species located in Europe and the Mediterranean countries. In Greece, chestnuts are widely spread among 28 districts of the country due to their diverse usages by humans (wood production, chestnuts, mushrooms, honey), while they can be geographically placed, based on the nuts’ morphological diversity in 6 main populations located in Kozani, Pilio, Karpenisi, Parnon, Lesvos and Crete. In this study, 56 trees from 3 different areas (Vamvakou, Varvitsa, Karyes) located in the west Parnon mountain region, were collected and subjected to genetic characterization with seven specific SSR molecular markers, in order to assess their genetic structure. The studied chestnuts exhibited a generally low level of genetic differentiation, with most of the genetic diversity residing within individual trees rather than being partitioned among different collection sites. Also, Karyes was not strongly genetically distinguished from Vamvakou and Varvitsa but the regions of Vamvakou and Varvitsa appeared to be genetically closely related compared to Karyes. The identified polymorphic microsatellite loci (especially CsCAT16 and CsCAT3) could be valuable tools for further, more detailed genetic studies of these chestnut populations.